PROFESI (SHAKILAH) (Dalam Perspektif Al-Qur’an) - Sulman Sulman; Muhammad Farhan (Jurnal Ushuluddin Adab dan Dakwah, 2020)
Profession comes from the Latin "Proffesio" which has two meanings, namely promise / pledge and work. If the meaning is made in a broader sense, it becomes an activity of "anything" and "anyone" to earn a living which is carried out with a certain skill. Whereas in a narrow sense profession means activities that are carried out based on certain expertise and at the same time it is demanded of proper implementation of social norms. Professions are groups of work fields that specifically carry out activities that require high skills and expertise in order to meet the complex needs of humans, in which use with the right way of high skills and expertise, profession is essentially an open statement or promise stating that a person is devoting himself to a position or service because that person feels called to take that job.